The construction of reinforced concrete beam for low-cost bungalow in Mukim Naga / Muhammad Ridwan Musa - Musa, Muhammad Ridwan (Universiti Teknologi MARA, Perak, 2022)
Because a reinforced concrete beam is necessary for every structure, this paper will outline the best practices for resolving the issue of reinforced concrete beams in residential structures. This investigation took place at the Mukim Naga. The goal of this report was to talk about the best way to build reinforced concrete beams. It will concentrate on how reinforced beams are made and how they are employed during the construction process. This study will also address a prevalent problem that affects the longevity and strength of reinforced beams. To debate the best way to fix and repair the damage on the beam in order to improve the beam's durability in the future.